Persepsi Mahasiswa Keperawatan Tentang Eskalasi Tenaga Perawat - Rendi Ariyanto Sinanto; Vivi Retno Intening (Dian Nuswantoro Semarang, 2021)
According to the Ministry of Health the number of nurse graduates per year is 46,865 people, the annual national need is 24,825, and the excess production of nurses is 11,067-22,060 per year. The increase in educational institutions has an impact on increasing graduates, nursing students are the generation of nurses, so this situation is very worrying to the nursing profession. The purpose of this study was to study the perceptions of Diploma 3 Nursing students at Bethesda Yakkum Yogyakarta Nursing School about the influence of nurses' workforce escalation. This study uses a Qualitative Design with a Phenomenology approach. The instruments used were human instruments with interview guidelines. The population was 61 Diploma 3 Nursing students in semester VI, samples were taken by purposive sampling of 5 participants. The analysis used is content analysis, and the triangulation technique used is source triangulation. This study shows students know the current condition of nurses, an increase in nurses makes students disappointed with the lecture process that has been undertaken, educational institutions increase so that graduates increase, but absorption is not optimal. This situation will result in unemployed nurses and nurses not working according to the profession. The hope of government students is to open up employment opportunities so nurses can contribute to the country in health development. Although students know about the escalation of nurses, but students are optimistic, confident in their abilities, will be entrepreneurial in health, and knowledge can be beneficial to the surrounding. Keywords: Nursing Students, Nurse Personnel, Nurse Escalation